Identifying another goldfields reporter: Frederick Dalton (1815–80). Issue 4 (1st October 2016) - Dalton, Brendan; Antonia, Alexis; Crabb, Peter; Craig, Hugh
Abstract: In a previous article, 'Who Wrote "A Visit to the Western Goldfields"?', our question was left unanswered. Further stylistic analysis has confirmed that this series and two subsequent ones published in the Sydney Morning Herald in the early 1860s were by the same author. Following a strong suggestion that this mystery author may have been Frederick Dalton, writings known to be by him were incorporated into the analysis. Since the only known writings of Dalton (until now) were mining reports, the stylistic analysis tests involved the comparison of writings in different genres. As well as a reporter, Dalton was a miner and geologist, in California as well as Australia, and subsequently a gold commissioner and mining warden in New South Wales. The identification of Dalton's considerable goldfields writings has enabled us to learn more of one of the pioneers of gold mining in New South Wales. This article has been peer reviewed.